2017
DOI: 10.1177/1687814017715420
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of negative external cost of green logistics and incentive mechanism

Abstract: The implementation of green logistics can reduce increasingly serious environmental damage while improving the operating efficiency of logistics enterprises. In this article, through quantitative calculation of logistics negative external costs, including traffic accidents, atmospheric pollution, noise pollution, and pollution caused by packaging, we build accounting standards to calculate the negative external costs of logistics enterprises that generate pollution mainly from transportation and packaging. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…To achieve the shipping sector's potential for decarbonization, it is necessary to calculate the external costs of CO 2 reductions. Full cost accounting in terms of external costs theory is applied (Antheaume, 2004;Mizutani et al, 2011;Frischmann and Marciano, 2015;Wang et al, 2017). For this purpose, tabularized datasets have been put together to show basic quantitative and qualitative data on global shipping [i.e., fleet size, deadweight tonnage (DWT) ( Supplementary Table 2), gross registered tonnage, main engine power output, and power generator output for commercial vessels (Supplementary Table 3)].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve the shipping sector's potential for decarbonization, it is necessary to calculate the external costs of CO 2 reductions. Full cost accounting in terms of external costs theory is applied (Antheaume, 2004;Mizutani et al, 2011;Frischmann and Marciano, 2015;Wang et al, 2017). For this purpose, tabularized datasets have been put together to show basic quantitative and qualitative data on global shipping [i.e., fleet size, deadweight tonnage (DWT) ( Supplementary Table 2), gross registered tonnage, main engine power output, and power generator output for commercial vessels (Supplementary Table 3)].…”
Section: Methodsmentioning
confidence: 99%
“…This means that ship-owning enterprises will have to immediately act to reduce ship-derived CO 2 emissions, while also striving to eliminate emissions. Hence, there arises a question as to the maritime shipping sector's potential for reducing CO 2 emissions, both in quantitative and monetary terms [i.e., reducing external costs (Antheaume, 2004;Wang et al, 2017)]. As such, this paper aims at evaluating approaches of the decarbonization process based on European Union (EU) strategic documents and low-emission and zero-emission technologies, used and developed, in maritime transport in the context of CO 2 emission reduction.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Arslan and Sar [68] found that the managers' intention towards green logistics initiatives is generally determined by the environmental attitude, perceived behavior control and subjective norm. Besides, government subsidizes [69] and internalization of externalities [70,71] were considered to be the effective models to reduce negative external cost in the logistics industry, thus promoting the greening process of the logistics market.…”
Section: Evaluation On the Social Environmental And Economic Impactsmentioning
confidence: 99%
“…From the perspective of the supply chain, this paper discusses the impact of multiple constraints on the economic feasibility of environmental investment and the potential to reduce externalities [9]. Wang et al (2017) established a model of internalization of logistics' negative external cost, and quantitatively analyzed the relationship between freight rates, freight volume, and the investments of enterprises in implementing green logistics. On the basis of comparing the two modes of "enterprise operation first" and "government subsidy first", this paper analyzes the effect of government subsidies.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of comparing the two modes of "enterprise operation first" and "government subsidy first", this paper analyzes the effect of government subsidies. The results show that the introduction of "government subsidy first" incentives and higher freight rates have contributed to the greening progress of logistics markets [10]. The above research basically explore a quantitative method of internalization of externalities from the perspective of industry and industrial chain.…”
Section: Introductionmentioning
confidence: 99%